Teacher Voices of Gender Representation in EFL Textbook: A case Study in a Senior High School - Wilfitri, Elvia; Suganda, Sonya Puspasari (English Department FBS UNP, 2023)
This research investigated teachers' perceptions regarding gender representation in two government-mandated English language textbooks used in Indonesian senior high schools. This research aims to examine the perceptions of teachers as users and implementers of textbooks regarding the existence of gender bias and stereotypes. This research used a qualitative method with a case study design. The research involved 2 participants, the English teachers who teach in grades 10 and grade 11. Semi-structured interviews were used as the instrument in this research. Analysis of interview data was transcribed manually and then interpreted critically in accordance with Creswell's theory. The findings from this study showed that both teachers expressed awareness of the gender bias and stereotypes present in the textbooks they used. Male representation is more dominant than female. Female roles tend to be placed in stereotypes constructed in society. The existence of certain ideologies is also the cause of unequal gender representation in textbooks. There is a need for continuous development and improvement of textbooks in order to promote equal gender representation. The pedagogical implications of the findings in this research proposed recommendations to educational institution sectors and language policy makers to prepare and publish textbooks that support the achievement of gender equality.